Dependence of the t(t)over-bar production cross section on the transverse momentum of the top quark - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; et al. (Elsevier B.V., 2010)
We present a measurement of the differential cross section for t (t) over bar events produced in p (p) over bar collisions at root s = 1.96 TeV as a function of the transverse momentum (p(T)) of the top quark. The selected events contain a high-p(T) lepton (l), a large imbalance in p(T). four or more jets with at least one candidate for a b jet, and correspond to 1 fb(-1) of integrated luminosity recorded with the D0 detector. Objects in the event are associated through a constrained kinematic fit to the t (t) over bar -> WbW (b) over bar -> lvbq (q) over bar' (b) over bar process. Results from next and next-to-next-to-leading-order perturbative QCD calculations agree with the measured differential cross section. Comparisons are also provided to predictions from Monte Carlo event generators using QCD calculations at different levels of precision. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Top quark; Differential cross sections; Perturbative QCD